The TNFα/Sphingosine-1-phosphate signaling axis drives myogenic responsiveness in heart failure - Kroetsch, Jeffrey T. (J Vasc Res, 2013)
Heart failure (HF) is hallmarked by an increase in total peripheral resistance (TPR) that compensates for the drop in cardiac output. While initially allowing the maintenance of mean arterial pressure at acceptable levels, the long term up regulation of TPR is prone to compromise cardiac performance and tissue perfusion and to ultimately accelerate disease progression. Augmented vasoconstriction of terminal arteries, the site of TPR regulation, is cooperatively driven by mechanisms like: (i) endothelial dysfunction, (ii) increased sympathetic activity, and (iii) enhanced pressure-induced myogenic responsiveness. Herein we review emerging evidence that the increase in myogenic responsiveness is central to the long-term elevation of TPR in HF. On a molecular level, this augmented intrinsic response is governed by an activation of the tumor necrosis factor α (TNFα)/sphingosine-1-phosphate (S1P) signaling axis in microvascular smooth muscle cells. The beneficial effect of TNFα scavenging strategies on tissue perfusion in HF mouse models adds to the gaining momentum to revisit the use of anti-TNFα treatment modalities in discrete HF patient populations.